2010
DOI: 10.1002/pssa.200983365
|View full text |Cite
|
Sign up to set email alerts
|

Reduced activation ODS ferritic steel – recent development in high speed hot extrusion processing

Abstract: The paper presents the microstructure and mechanical properties of an oxide dispersion strengthened (ODS), reduced activation, ferritic steel, namely the Fe-14Cr-2W-0.3Ti-0.3Y 2 O 3 alloy, which was fabricated by hot isostatic pressing followed by high speed hydrostatic extrusion (HSHE) and heat treatment HT at 1050 8C. Transmission electron microscopy (TEM) observations revealed significant differences in the grain size and dislocation density between the as-HIPped and as-HSHE materials. It was also found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Finally, severe plastic deformation (SPD) processes such as equal channel angular extrusion (ECAE) or pressing (ECAP) and high-speed hot extrusion (HSHE) have also applied to ODS steels. [12,47,48] Both HSHE and ECAE of the as-HIPed material were shown to give rise to a significant microstructure refinement and extra hardening. [47,48] However, SPD applied to PM ODS steels may not offer a major step forward from an economic point of view.…”
Section: B Recent Progress In Powder Processing Of Ods Alloysmentioning
confidence: 97%
“…Finally, severe plastic deformation (SPD) processes such as equal channel angular extrusion (ECAE) or pressing (ECAP) and high-speed hot extrusion (HSHE) have also applied to ODS steels. [12,47,48] Both HSHE and ECAE of the as-HIPed material were shown to give rise to a significant microstructure refinement and extra hardening. [47,48] However, SPD applied to PM ODS steels may not offer a major step forward from an economic point of view.…”
Section: B Recent Progress In Powder Processing Of Ods Alloysmentioning
confidence: 97%
“…Such a processing results in reduced grain size and residual porosity, bringing about improved strength and impact properties [10]. Extruded samples were annealed at temperature ranging from 650 up to 1350°C, for 1 h in argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that fine and thermo-stable oxides improve the creep resistance of ferritic steels [ 10 , 11 , 12 , 13 ] and trap He in fine bubbles, thereby limiting He movement and restraining He brittleness [ 2 , 3 , 4 ]. The common processes to fabricate ODS steels are powder metallurgy (PM) with mechanical alloying (MA) and heat consolidation [ 14 ], including hot isostatic pressure (HIP) [ 9 ], hot extrusion (HE) [ 15 , 16 ], and spark plasma sintering (SPS) [ 17 ], and ODS steels have a high density and an excellent tensile strength. In contrast to HIP and HE, laser additive manufacturing (LAM) [ 18 , 19 ] without the MA process is a method used to manufacture the ODS Fe-matrix alloys because of its low cost and flexibility [ 18 ].…”
Section: Introductionmentioning
confidence: 99%